2022
DOI: 10.1155/2022/7332324
|View full text |Cite
|
Sign up to set email alerts
|

Development of Electron Paramagnetic Resonance Magnet System for In Vivo Tooth Dosimetry

Abstract: As part of a homebuilt continuous wave electron paramagnetic resonance (EPR) spectrometer operating at 1.2 GHz, a magnet system for in vivo tooth dosimetry was developed. The magnet was designed by adopting NdFeB permanent magnet (PM) for the main magnetic field generation. For each pole of the magnet, 32 cylindrical PMs were arranged in 2 axially aligned ring arrays. The pole gap was 18 cm, which was wide enough for a human head breadth. The measured magnetic field was compared with the magnetic field distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A 1.15 GHz continuous wave EPR spectrometer developed in previous studies was used for the EPR measurements (Park et al 2021; Choi et al 2022). The EPR dose-response data were collected from the teeth with and without the pseudo-in-vivo phantom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1.15 GHz continuous wave EPR spectrometer developed in previous studies was used for the EPR measurements (Park et al 2021; Choi et al 2022). The EPR dose-response data were collected from the teeth with and without the pseudo-in-vivo phantom.…”
Section: Methodsmentioning
confidence: 99%
“…It can measure and assess one subject in a few minutes with high throughput, and it is relatively easily operated by less skilled operators. Furthermore, in several previous studies, in vivo EPR devices had been developed in light and compact forms so that they can be directly carried with a vehicle to the location of the counter-accident (Williams et al 2011a; Choi et al 2022). Moreover, in vivo EPR tooth dosimetry is a unique technique to measure human subjects noninvasively.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the UV-generated EPR signal was minimal compared to doses relevant for triage, with a lifetime effect of 0.33 Gy (a lifetime of 50 y of exposure of these teeth), well below the 2.0 Gy threshold for triage. Choi et al (2022) developed a magnet system for in vivo tooth dosimetry, operating at 1.2 GHz, as part of a homebuilt continuous wave (CW) EPR spectrometer. The magnet, employing NdFeB permanent magnets, demonstrated a wide pole gap suitable for a human head.…”
Section: In Vivo Electron Paramagnetic Resonance (Epr) Tooth Enamel D...mentioning
confidence: 99%